17: Afro-centric law and technology discourse - Ncube, Caroline B. (Edward Elgar Publishing, 2023)
This chapter considers Afro-centric anglophone literature on law and technology to decipher dominant themes and approaches. Our scoping study demonstrated a rich and growing body of work on a broad range of topics including privacy in health and biometric data, data governance, the regulation and impact of Artificial Intelligence and other 4IR technologies as well as technology and gender, democracy and human rights. This richness or depth is due to the literature's grounding in Africa's political, socio-economic context and developmental imperatives. Consequently, there is a strong thematic focus on development, social justice and human rights as well as neo-colonialism and decoloniality with emphasis on feminist perspectives. From which ever perspective scholars take, their shared bottom line is that regulation of technology needs to be carefully nuanced for African contexts to ensure that historical extractive patterns are severed and that legal frameworks do not exacerbate inequality or deepen the digital divide.